Unprecedented diterpene skeletons isolated from vascular plants in the last twenty years (2001–2021). (December 2022) - Chacón-Morales, Pablo A.
Abstract: Every year there are hundreds of reports about the isolation of undescribed terpenoids based on novel functionalizations of known carbocyclic skeletons series. However, on some occasions the compounds obtained have a carbocyclic skeleton that does not correspond with the series established, in these peculiar opportunities, in addition to finding an undescribed natural product, is obtained an unprecedented carbocyclic skeleton, whose biogenesis must necessarily involve other additional steps that explain its formation. This review accounts for the reports of seventy-nine unprecedented diterpene skeletons (corresponding to one-hundred-three undescribed diterpenoids) isolated from vascular plants in the last two decades. According to the genus, Euphorbia and Salvia are the most prolific in reports of unprecedented diterpene skeletons with a total of twenty, and nine skeletons, respectively. If the findings are expressed in terms of the family, Euphorbiaceae and Lamiaceae have the highest number of reports of undescribed diterpene skeletons, with twenty-seven and twenty-two, respectively. Finally, fifty-three skeletons are derived from higher diterpenoids (2 –12, 68, 69, 86, 104 –109, 158 –161, 186, 189, 222, 250 –255, 285 –298, 403 –404, 415, 416, and 436 ), twenty are derived from lower diterpenoids (135, 136, 192 –194, 225 –229, 363 –370, 397, and 425 ), and six (96, 97, 147, 148, 205, and 206 ) are derived from skeletons whose biogenesis has not yet been established, or at least, cannot be formally included within the groups mentioned above. This article comprehensively highlights the hypothetical biosynthetic pathway for each of the one-hundred-three undescribed compounds with unprecedented diterpene skeletons and summarizes their most significant biological activities. Graphical abstract: The isolation of 79 unprecedented diterpene skeletons (corresponding to 103 novel diterpenoids) from vascular plants in the last two decades were summarized. All diterpenoids were classified according to the parent structure proposed in their respective biosynthetic pathways. Image 1 Highlights: The isolation of 79 unprecedented diterpene skeletons are summarized. All diterpenoids are classified according to the proposed parent structure. The proposed biosynthetic pathway for each diterpenoid is represent in detail. The biological activities of the undescribed diterpenoids are summarized.